Employe Self-Acceptance in the Human Resources Development (HRD) Department at PT Cabinindo Putra in Facing Work Responsibilities - Laila Azizah; Nursyaniah Siregar; Putri Satya Permana; Rajif Fadillah Muhammad; Netty Merdiaty (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Employe psychological well-being is an important aspect that not only affects individuals but also the sustainability and effectiveness of the organization. One of the internal factors that plays an important role in shaping psychological well-being is self-acceptance. This study aims to understand the self-acceptance and psychological well-being of employes, specifically Human Resource Development (HRD) staff at PT Cabinindo Putra, a manufacturing company with high work demands related to accuracy, speed, and consistency. This research uses a qualitative approach with data collection methods including in-depth interviews and focus group discussions (FGD). Data analysis is based on Ryff's theory of psychological well-being and Berger's concept of self-acceptance. The research results show that HRD at PT Cabinindo Putra has a good level of self-acceptance, as evidenced by confidence in one's abilities, the use of internal value standards, a responsible attitude toward mistakes, the ability to accept criticism objectively, and a realistic understanding of one's limitations. This condition supports the creation of emotional stability and positive psychological well-being in carrying out the strategic role of HRD. This research is expected to provide an overview of the importance of self-acceptance as a foundation for employe psychological well-being and to be a consideration for organizations in human resource development.